Focal myositis and contracture secondary to amiodarone extravasation from a peripheral cannula. Issue 1 (18th January 2019) - Ledingham, David; Cordato, Dennis
Abstract : A 63-year-old man underwent cardioversion of atrial fibrillation with intravenous amiodarone through an antecubital fossa cannula. Mid-infusion, the cannula tissued. He developed immediate pain and swelling. At 3 weeks, he continued to have significant pain and had developed a fixed flexion deformity. MRI demonstrated focal myositis of the biceps and brachialis muscles. Treatment included physiotherapy and plastic surgery but sadly in spite of this, the patient has had minimal symptomatic improvement at 1 year. Amiodarone extravasation is well recognised to cause local injection site reactions. Involvement of deeper tissues is rare. To our knowledge, this is only the second description of a consequent focal myositis in the literature.